A guide for soil biology training - Kaushal, Manoj (2023)
Nature positive agriculture initiative offers sustainable food production system that meet the demands of growing population as well as facilitating the necessity of environmental restoration, biodiversity conservation thereby improving soil, land and water by scientifically supported solutions. Nature positive implement and equitably support food and livelihoods on the ground through a transformative change, initiating at farm and community-level, mainstreaming the research pathways and solutions in the smallholder agricultural systems. While working and implementing solutions with CGIAR and non-CGIAR partners including decision makers, the initiative also accounts true food cost, target the policy realignments and incentives for higher adoption rate of nature positive solutions. Finally, the initiative aims to protect, manage and restore natural ecosystems, enhance soil biodiversity, mitigate climate change and shift overall food systems to net nature-positive way.